Exploring the Philippine economic landscape and structural change using the input-output framework - Nedelyn Magtibay-Ramos; Gemma Estrada; Jesus Felipe (Levy Economics Institute of Bard College, 2010)
This paper explores the degree of structural change of the Philippine economy using the inputoutput framework. It examines how linkages among economic sectors evolved over 1979-2000, and identifies which economic sectors exhibited the highest intersectoral linkages. We find that manufacturing is consistently the key sector in the Philippine economy. Specifically, resourceintensive and scale-intensive manufacturing industries exhibit the highest linkages. We also find a growing impact on the economy of private services and transportation, communication, and storage sectors, probably due to the globalization of these activities. Overall, however, the services sector exhibits lower intersectoral linkages than the manufacturing sector. We conclude that the Philippines cannot afford to leapfrog the industrialization stage and largely depend on a service-oriented economy when the potential for growth still lies primarily in manufacturing.
Keywords: D57; L60; O11; 330; input-output analysis; linkage index; multiplier product matrix; structural change; Entwicklung; Branche; Input-Output; Philippinen